"Combining equity and utilitarianism"—additional insights into a novel approach. (17th May 2017) - Gerdessen, Johanna C.; Kanellopoulos, Argyris; Claassen, G.D.H. (Frits)
Abstract: Recently, a novel approach (to be referred to as CEU) was introduced for the frequently arising problem of combining the conflicting criteria of equity and utilitarianism. This paper provides additional insights into CEU and assesses its added value for practice by comparing it with a commonly used extended goal programming (EGP) approach. The comparison comprises the way of balancing equity and utilitarianism, the number and spacing of solutions, discrete versus continuous nature, method‐specific parameters, distance to the Pareto front, and computational effort. CEU balances between equity and utilitarianism in a way that is basically different from using a convex combination of these two criteria. Moreover, CEU's parameter has an intuitive interpretation. The set of solutions generated by CEU is smaller and more widely spaced than EGP's set of solutions, which can be an advantage for the decision maker. CEU generates solutions on the Pareto front of the decision maker's n ‐criteria problem. However, CEU's way of balancing equity and utilitarianism causes a (small) distance to the Pareto front of the associated bicriteria problem on the aggregate criteria. Reporting this distance will support the decision maker to assess whether the achieved balance is worth its price. Using CEU may require a larger computational effort than using EGP.